2014
DOI: 10.3109/14647273.2013.872301
|View full text |Cite
|
Sign up to set email alerts
|

Systematic evaluation of the quality of clinical practice guidelines on the use of assisted reproductive techniques

Abstract: The overall quality of the CPGs on Assisted Reproduction Techniques published during the last 5 years is suboptimal. Most Guidelines present significant shortcomings in important domains such as "stakeholder involvement", "rigor of development", and "applicability". Instruments such as the AGREE II and "the Grading of Recommendation Assessment Development and Evaluation" system could prove useful to improve CPGs in this field. Guideline users could benefit from the present results when choosing which guideline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
0
3
0
1
Order By: Relevance
“…Due to the problems described above, some researchers criticize that AGREE II allows no clear distinction between high- and low-quality guidelines [ 33 , 47 , 48 , 54 ]. Several researchers use cut-offs to distinguish between high and low quality [ 32 , 44 , 50 , 55 60 ]. This shows that AGREE II users would welcome such a clear distinction, but the instrument currently does not fulfil this requirement.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the problems described above, some researchers criticize that AGREE II allows no clear distinction between high- and low-quality guidelines [ 33 , 47 , 48 , 54 ]. Several researchers use cut-offs to distinguish between high and low quality [ 32 , 44 , 50 , 55 60 ]. This shows that AGREE II users would welcome such a clear distinction, but the instrument currently does not fulfil this requirement.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8] To evaluate the quality of the guidelines for assisted reproductive technology, some previous studies using AGREE II have already been published, which showed the poor quality of current guidelines. [9,10] However, AGREE II was created by a small group of researchers, and did not separate out reporting and methodological quality of guidelines. The exact reporting quality of the guidelines is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the lack of standardized instruction for the assessments, the overall assessments become highly subjective 27,28,64 . Although several previous appraisals 65,66 use the 60% cut‐off score, we think the value is somewhat arbitrary. Instead, we conducted the overall quality by having two assessors to rate the quality.…”
Section: Discussionmentioning
confidence: 99%